Uji Aktivitas Enzim Selulase Baglog Jamur Pleurotus cystidiosus, Pleurotus ostreatus dan Auricularia auricula dengan Pelarut Berbeda - Astri Zulfa; Tsabitah Athifah Qonitah; Safendrri K Ragamustari; Vivitri Dewi Prasasty (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Cellulase enzyme activity is essential for the breakdown of cellulose, a major component of plant cell walls. This enzyme is produced by a variety of microorganisms, including fungi such as mushrooms. This study aimed to evaluate the cellulase enzyme activity extracted from the baglogs of three different mushrooms: Pleurotus cystidiosus (brown oyster mushroom), Pleurotus ostreatus (white oyster mushroom), and Auricularia auricula (wood ear mushroom). The extraction was conducted using three different solvents: aquadest (distilled water), saline solution, and citrate buffer at pH 4. The cellulase activity was assessed under optimal conditions of 60 °C incubation temperature and 60 minutes incubation time. The results indicated that the lowest cellulase activity was found in the baglogs of Pleurotus cystidiosus extracted with aquadest, measuring at 0.0253 IU/mL. Conversely, the highest cellulase activity was observed in the baglogs of Pleurotus ostreatus extracted with aquadest, with an activity level of 0.0728 IU/mL. The glucose concentration, which serves as an indicator of the enzymatic hydrolysis of carboxymethyl cellulose (CMC), was highest in Pleurotus ostreatus extracted with aquadest at 393.043 ppm. These findings suggest that Pleurotus ostreatus is the most effective species for cellulase production among the tested mushrooms when extracted with aquadest. The optimal extraction and assay conditions determined in this study can guide future research and industrial applications in enhancing cellulase enzyme production from mushroom baglogs, particularly in bioconversion processes and bioethanol production.